Problem-based learning with role-playing: An experiment on prospective mathematics teachers - Ita Chairun Nissa; I Ketut Sukarma; Sutarto Sutarto (Universitas Islam Negeri (UIN) Mataram, 2020)
[English]: This study aimed to examine the effect of problem-based learning (PbL) with role-playing toward problem-solving skills of prospective mathematics teachers’ (PMTs) who take linear algebra courses. The study was a quasi-experimental with a non-equivalent control group post-test only design. Forty-two PMTs were involved and divided into experimental (taught using PbL combined with role-playing) and control groups (taught using PbL only). Data were collected using tests and video recordings. The test produces data on PMTs' problem-solving skills on linear algebra problems and video recordings resulted in the transcripts of PMTs’ discussion when they played a role. Data were analyzed through two stages. Firstly, the results of the test were analyzed quantitatively using F-test to measure the variance of the two groups, then measure the normality of the data using the interpretation of skewness and kurtosis, and finally, one-tail t-test to measure differences in test results between the two groups. Secondly, the sample of PMTs’ works in two groups and the transcripts of their conversation were qualitatively analyzed to strengthen the quantitative finding and reveal how PbL with role-playing support PMTs’ problem-solving in teacher education. This study shows that PbL with role-playing is more effective to improve students’ problem-solving skills than solely doing problem-based learning. Doing a role-playing provided students with the opportunity to be able to think and speak mathematics more formally in the context of problem-solving. Keywords: Problem-based learning, Role-playing, Prospective mathematics teachers, Problem-solving [Bahasa]: Penelitian ini bertujuan untuk menguji pengaruh pembelajaran berbasis masalah dengan bermain peran pada pemecahanmasalah calon guru matematika yang mengambil matakuliah aljabar linier pada semester ketiga. Penelitian ini adalah eksperimen semu dengan desain post-test kelompok kontrol yang tidak setara. Empat puluh dua calon guru matematika terlibat dalam penelitian ini dan mereka dibagi menjadi kelompok eksperimen (diajarkan menggunakan pembelajaran berbasis masalah dengan bermain peran) dan kelompok kontrol (diajarkan menggunakan pembelajaran berbasis masalah saja). Data dikumpulkan menggunakan tes dan rekaman video. Tes menghasilkan data tentang kemampuan calon guru untuk memecahkan masalah aljabar linier dan rekaman video yang menghasilkan transkrip diskusi calon guru ketika mereka memainkan suatu peran. Data dianalisis melalui dua tahap. Pertama, hasil tes dianalisis secara kuantitatif menggunakan uji-F untuk mengukur varian kedua kelompok, kemudian mengukur normalitas data menggunakan interpretasi skewness dan kurtosis, dan akhirnya dilakukan uji-t satu pihak untuk mengukur perbedaan hasil tes antara kedua kelompok. Kedua, sampel hasil tes calon guru matematikadari kedua kelompok dan transkrip diskusidianalisis secara kualitatif untuk memperkuat temuan kuantitatif dan mengungkapkan bagaimana pembelajaran berbasis masalah dengan bermain peran dapat mendukung pemecahan masalah pada calon guru matematika yang menempuhpendidikan guru. Penelitian ini menunjukkan bahwa pembelajaran berbasis masalah dengan bermain peran lebih efektif untuk meningkatkan keterampilan pemecahan masalah calon guru matematika daripada hanya melakukan pembelajaran berbasis masalah saja. Bermain peran memberikan kesempatan kepada mahasiswa untuk dapat berpikir dan mengomunikasikan matematika secara formal dalam konteks pemecahan masalah. Kata kunci: Pembelajaran berbasis masalah, Bermain peran, Calon guru matematika